How are we preparing doctors for their roles as patient educators? Exploring undergraduate and postgraduate curricula in Canadian medical schools - Cohen, Alexandra; Gomez-Garibello, Carlos; Steinert, Yvonne (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
Background: Although patient education (PE) has been identified as an important strategy to support patients with low health literacy, medical trainees report feeling ill-prepared for this responsibility. Our goal was to explore how PE training is incorporated centrally into undergraduate (UGME) and postgraduate (PGME) education across Canada, with the aim of proposing a PE curriculum.Methods: We circulated a web-based survey to all Canadian UGME and PGME Associate Deans, subsequently expanding the scope of our investigation by surveying Family Medicine and Pediatrics program directors. Data analysis involved a combination of frequency calculations and conventional qualitative content analysis.Results: According to survey respondents, PE was taught centrally in 72% of UGME curricula, 25% of PGME curricula, and 25% and 82% of Pediatrics and Family Medicine programs respectively. PE was predominantly incorporated into communication skills curricula, and role modeling was the most common teaching modality. Barriers included lack of time and low curricular priority; facilitators included embedding PE into communication skills training and use of patient partners and standardized patients.Conclusions: PE has not been uniformly implemented in a centralized manner across Canadian UGME and PGME curricula. Based on our survey data and the relevant literature, we propose a sample longitudinal curriculum spanning UGME and PGME and recommend that PE be explicitly framed as a communication skill.